Mechanisms of adipose tissue extracellular matrix alterations in an in vitro model of adipocytes hypoxia and aging. (December 2020) - Zoico, E.; Policastro, G.; Rizzatti, V.; Nori, N.; Darra, E.; Rossi, A.P.; Fantin, F.; Zamboni, M.
Highlights: Aged 3T3-L1 adipocytes were characterized in vitro by significant increase in gene expression of pro-inflammatory cytokines and ECM components. Aged adipocytes presented an increase in cellular senescence, not present in hypoxic adipocytes, as well as an increase in HIF-1a and in ROS. Immunofluorescence and western blot analysis revealed a significant decrease in caveolin-1 expression in aged adipocytes. We hypothesized caveolin-1, reduced in senescent adipocytes, as a potential link between aging and fibrosis. Abstract: Fibrosis has been considered as a hallmark of dysfunctional adipose tissue (AT), however the role and mechanisms of fibrosis in the age related AT dysfunction are not yet well characterized. The aim of the study was to investigate the mechanisms of extracellular matrix (ECM) alterations and the role of caveolins, using an in vitro model of adipocyte aging and hypoxia. Hypoxic adipocytes, but also aged adipocytes, were characterized by a significant increase in gene expression of pro-inflammatory cytokines and ECM components. Immunofluorescence analysis confirmed an increase in collagen VI-A3 in hypoxic and also in aged adipocytes. However aged adipocytes were characterized by only a slight increase in HIF1α immunofluorescence and by a more relevant increase in senescence compared to hypoxic and mature adipocytes, with an increase in p-53 protein and a decrease in SIRT 1 protein. Immunofluorescence and western blot analysis revealed a significant decrease in caveolin-1 expression in hypoxic adipocytes and even more in aged adipocytes. In conclusions, aging adipocytes are associated to alteration of ECM and fibrosis, by modulation of the caveolins through complex mechanisms where inflammation, hypoxia and cellular senescence are coexisting.